DESIGN OF INTEGRATED PHARMACY INFORMATION SYSTEMS USING SERVICE ORIENTED ARCHITECTURE - Haq, Azizi Khoirul; Fauzi, Muhammad Dzulfikar; Mustakim, Muhammad (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
Pharmacy information systems that exist today, many of them are designed and built just to manage a single specific pharmacy. In terms of ordering medications, the pharmacies most still use the manual method, such as send a letter of reservation or make a reservation by phone. The database is built as a back-end of the pharmacy information system, also use the software most diverse database. Currently, from the customer side, to obtain the presence information of a drug product, customers need to go to every pharmacy one by one to find the product you are looking for drugs. This, of course, will add to the cost and is very inefficient in economic terms. This study aims to develop an integrated pharmacy information system by utilizing Service Oriented Architecture. Method of system development approach is built with Systems Development Life Cycle (SDLC). Plans are being implemented by the Unified Modeling Language (UML). The programming language used in this study is PHP with CodeIgniter framework, Visual Basic. NET (VB.NET), and Java 2 Mobile Edition (J2ME). The results of this research are the production of an integrated pharmacy information system with other pharmacy information system and other applications, both in terms of different languages and different development in the database used. With the integration of the system, it can be used for broader uses, such as ordering goods between different pharmacy systems. In addition, it also produced mobile and desktop-based applications to access information drug stocks. These mobile applications are expected to be able to close the pharmacy with a customer who would have an impact on customer relationships and the pharmacies are getting close.